Asymmetric Dual‐Reagent Catalysis: Mannich‐type Reactions Catalyzed by Ion Pair1. Issue 6 (16th December 2014) - Wang, Hong‐Yu; Zhang, Kai; Zheng, Chang‐Wu; Chai, Zhuo; Cao, Dong‐Dong; Zhang, Jia‐Xing; Zhao, Gang
Abstract The combination of a new bifunctional phosphine and an acrylate generate a zwitterion in situ and it serves as an efficient catalyst for asymmetric reactions through a homogeneous ion‐pairing mode. This new catalytic system has been successfully applied to Mannich‐type reactions to give excellent results and it demonstrates a broad substrate scope. Such reactivity is not accessible with general organophosphine catalytic modes. Preliminary investigations into the mechanism are also presented.